Dynamic Characteristics and Effect on Thrust of Jet Tail Vortex Ring for Pump Jet Propulsion - Han, Wei; Li, Zhixiong; Li, Rennian; Feng, Huimin; Nan, Lingbo; Xu, Jun; Xiao, Mingzhen (Frontiers in Energy Research, 2022)
Jet tail vortex ring is the turbulent coherent structure at jet flow wake area of the pump injection. In this paper, a method which is combed numerical simulation and vortex dynamics is adopted, which analysis the dynamic characteristics and influence on the thrust characteristics of water jet propulsion pump. A large eddy simulation turbulence model and a dimensionless water jet propulsion pump velocity coefficient were used to reveal the flow structure and relation, with the pump operation parameters of wake vortex ring. The thrust with a trailing vortex ring is 7.0/% higher than that without a trailing vortex ring. Vortex dynamics and mathematical statistics are combined to quantitatively analyze the dynamic characteristics of jet tail vortex ring. Finally, the formation time of vortex ring is obtained in exponential relation with dimensionless transmission velocity and vorticity coefficient, which has nonlinear relation with vortex intensity coefficient and helicity coefficient. BP neural network combined with LM algorithm is used to establish the mathematical relationship between thrust and physical characteristic parameters of vortex ring.